Household environmental microbiota influences early‐life eczema development. (12th August 2021) - Ta, Le Duc Huy; Tay, Carina Jing Xuan; Lay, Christophe; de Sessions, Paola Florez; Tan, Cheryl Pei Ting; Tay, Michelle Jia Yu; Lau, Hui Xing; Zulkifli, Atiqa Binte; Yap, Gaik Chin; Tham, Elizabeth Huiwen; Ho, Eliza Xin Pei; Goh, Anne Eng Neo; et al.
Summary: Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces, Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces, Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment. Abstract : The study findings of S‐PRESTO are depicted in the infographic. Dust microbiota composition of bed dust and living room floor dust was compared between houses of subjects with and without eczema. Increased abundance of human‐associated bacteria Actinomyces, Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium was associated with eczema development, suggesting the possible regulation of host immunity resulting in atopy. Conversely, Planomicrobium, an environmental bacterium, was found to possibly prevent the development of eczema by inhibiting proinflammatory human‐associated bacteria. Exposure to natural environmental microbiota may be needed to modulate shed human associated microbiota in an indoor environment.